BRAND IMAGE RESTORAN CEPAT SAJI BAGI KALANGAN REMAJA DI KOTA PADANG - Putra, Teguh Hadi; Silfeni, Silfeni; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This research is motivated young people in the city of Padang whogenerally prefer food in fast food restaurants that have differences in thepopularity of several types of fast food restaurants. Teens tend to prefer fast foodrestaurants although had to queue to order food and expensive prices. This studywas to describe the brand image of fast food restaurants for teenagers in the cityof Padang. This research is descriptive quantitative. The population in this studywere young in Padang amounted to 37 591. The sample in this study amounted to99 respondents. The sampling technique acquired through non-probabilitysampling method with purposive sampling. Deploy data collection techniquesbased on Likert Scale questionnaire. Data analysis covers: validity and reliability.Overall brand image of fast food restaurants in the average score of 140.71 in therange of 125 - <148 with image indicators is well. Be based category average of59.54 manufacturers currently on the score 53 - <63 in both categories, theindicator average consumer image 47.84 in the range be at the score> 50 withvery good category, the indicator image of the product at an average of 33.34 wasthe score 31 - <37 with both categories.Keywords: Brand Image, restaurant, Teens